Certification Relics: Entrepreneurship Amidst Discontinued Certifications - Eberhart, Robert N.; Armanios, Daniel Erian (Organization Science, 2022)
We explore a key tension between certification and entrepreneurial entry. On the one hand, more stringent certifications may provide greater legitimacy. On the other hand, market entry may be facilitated by easing such standards. To reconcile this tension, we examine discontinued certifications. We draw on research into how new ventures use certifications to gain legitimacy, along with quantitative data from new venture credit records. We show that after a certification is discontinued, new ventures in emerging industries continue to conform to these discontinued certified standards. Our study shows that those whose attributes do not provide other sources of legitimacy (e.g., unconventional founders in emerging industries) are more likely than other new ventures to comply with discontinued certification. However, those with other legitimating attributes (e.g., elite institution alumni founders) can overcome such legitimacy deficits and take advantage of new rules easing entry. Overall, our findings show that discontinued certifications can become certification “relics” whose standards continue to linger and influence entry, even after they are no longer formally in effect. Our study and its findings enhance our understanding of institutional support for new ventures, as well as the repertoire of strategic actions available to new ventures to gain legitimacy and acceptance in the face of institutional change.